The teacher as researcher in the classroom - Bolaños Motta, José Ignacio (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper is inspired by the song titled ¨La fábula de los tres hermanos (The Tale of the Three Brothers), by the Cuban singer Silvio Rodriguez Dominguez. The hope is to reflect on the creation of research projects at the high school level, or as it is presently called, classroom research, through three excerpts, consequently selected from the lyrics of this song. This work deals with the complications, topics, and other issues that eventually occur in the multiplicity of daily commitments with which the teacher is confronted, when developing research in an educational community using ethnography; methodology currently used in research education and pedagogy models. This document aims to assert the high school teacher’s gaze when investigating the context of scholarly work, and the role of the universities in regard to the teacher training on educational research competencies.